Customer Attitude Towards Mobile Advertising - Acharya, Paras Mani (Damak Campus Journal, 2024)
Mobile Advertising is now emerging as a new channel of marketing communication. The major objectives of this descriptive research are to examine the customer attitude towards mobile advertising. The researcher has used convenience sampling method and collected 100 samples from the respondent located at Damak. The data collected through the questionnaire were organized and analysed using SPSS and Microsoft Excel. From result, indicate a significant relationship between all independent variables and the dependent variable, which is customer attitude. Among the various independent variables, credibility emerges as the most influential factor shaping customer attitude towards mobile advertising. This suggests that individuals perceive mobile advertising as a reliable and trustworthy source, often using personalized content as a reference for their purchasing decisions.